Dealing with Emergency Remote Teaching: The Case of Pre-Service English Language Teachers in Turkey - Reyhan Ağçam; Yunus Emre Akbana; Stefan Rathert (National Research University Higher School of Economics, 2021)
Education has been offered in the form of Emergency Remote Teaching (ERT) worldwide since March 2020 due to the spread of Covid-19. This compulsory transition has often been marked by disregard of the technological infrastructure of educational institutions, digital literacy skills of teachers and students, and their access to technology. A growing body of research discusses challenges faced in ERT; however, further studies are needed to arrive at validated conclusions to inform formal language teaching and learning. Against this backdrop, this qualitative study aimed at adding context-dependent knowledge to the literature by reporting on the case of university students majoring in language teaching. For this reason, the perceptions of a group of 67 pre-service English language teachers on ERT practices at a Turkish state university were explored. Data were collected through an interview form developed by the researchers and a focus group interview. The data were analysed inductively using content analysis. Half of the participants reported that specific skills were conducive to doing tasks in an ERT environment. They not only reported a variety of challenges related to the perceived ineffectiveness of learning, technical insufficiency, and inappropriateness of the learning environment, but also acknowledged contributions to their personal and academic development. That is, they found ERT flexible, time-saving, and favourable for learners who felt more confident in virtual classrooms, and some considered ERT as an opportunity for self-actualisation. Nonetheless, the majority favoured face-to-face education over ERT appreciating the enhanced effectiveness of in-class education. In sum, the study emphasises the need to support learners and teachers by providing instructions and strategies on how to organise learning and teaching. Moreover, schools, policy makers, and governmental authorities may need to provide ERT-tailored programmes and an infrastructure in terms of technical equipment to meet the requirements of education delivered in ERT and to realise effective language learning in virtual environments. Broadening the knowledge base concerning ERT in language teacher education, this study advises to address drawbacks of ERT and to take advantage of its opportunities.